Parameterization of Educational Activities in an Educational Institution of Higher Education - A. I. Mosalev (Открытое образование (Москва), 2023)
Purpose of the study. The formulation of a program of educational work in universities is one of the most important in the framework of the formation of the personality of a graduate. However, the rules for the formation of such a program are framework and are based on the state strategy of educational activities, as well as in accordance with the profile of the educational institution itself. Such an «open» state of the formation of programs, of course, gives advantages in the freedom to choose the trajectories of educational work with students; however, it also leaves an imprint on the possibility of fully considering the interests of all aspects of the educational process. It is important to form a vision of how, what parameters will consider the opinion of not only the leadership of the educational institution, the teaching staff, but also the students themselves, as well as their parents.Materials and methods. The basis for the study was the materials of the regulatory framework and theoretical articles in the field of educational activities. Emphasis was placed on a systematic analysis of the relationship of educational practices with an eye on the value orientations of today’s youth. In terms of developing proposals, the method of an online questionnaire survey of students, parents and legal guardians, teaching staff, faculty management, as well as representatives of departments in whose competence are issues of educational activities was used.Results. Maps for assessing the parameters of educational work have been developed in the context of spiritual, moral, and socio-axiological parameters. Based on the analysis, it was possible to structure both the strengths of the educational practice of the university, as well as weaknesses that are important to pay attention to. As a result, the approach described in the article allows an educational institution, when forming its own program of educating students, determining the development trajectories of each student, to understand what problems and misunderstandings may arise in the system plan, and to determine for themselves what individual parameters of educational contexts are important to focus on.Conclusion. The author is working on the systematization of the practices of the educational process through the systemic decomposition of the individual components of the programs of educational work with students at the university. Questions that require further research – what should be the indicative indexes and tools for measuring them, as well as the frequency of such work. Therefore, for example, it draws attention to what metrics will allow assessing the degree of development of internal feelings among students as will, justice, faith in goodness, etc.